Design and Implementation of a Wilkinson Power Divider with Integrated Band Stop Filters Based on Parallel-coupled Lines - Phromloungsri, Ravee; Sonasang, Somchat (Applied Computational Electromagnetics Society Journal (ACES), 2023)
This paper presents a technique to improve the spurious suppression performance at the second harmonic (2f0) of a Wilkinson power divider. The technique is achieved by the insertion of bandstop filters realizing with parallel-coupled lines with the characteristic impedance of 2√Z0Ω and the electrical length of λ/8 in a conventional structure. The simulated and measured results of the conventional and the proposed divider are compared at 0.9 GHz. The insertion losses (S21, S31) are less than 3.1 dB, while the return losses (S11) are less than 34.6 dB across 100% fractional bandwidth. Moreover, the proposed Wilkinson power divider achieves more than 25.5 dB suppression at 2f0.